2015
DOI: 10.1097/bsd.0b013e3182a9435e
|View full text |Cite
|
Sign up to set email alerts
|

Does Navigation Improve Accuracy of Placement of Pedicle Screws in Single-level Lumbar Degenerative Spondylolisthesis?

Abstract: O-arm navigation does not provide any significant advantage over conventional free-hand pedicle screw insertion technique in patients with single-level degenerative spondylolisthesis. The accuracy is dependent on the distance of the tracker from the level of instrumentation. Lateral perforations are more common because of instability at the instrumented level leading to translation and rotation of the vertebral body while placing pedicle screws leading to preferential lateral trajectory. These lateral perforat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…However, O-arm navigation does not provide any significant advantage over conventional free hand pedicle screw insertion technique. 21 [ ( F i g . _ 7 ) T D $ F I G ] Our technique is (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, O-arm navigation does not provide any significant advantage over conventional free hand pedicle screw insertion technique. 21 [ ( F i g . _ 7 ) T D $ F I G ] Our technique is (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3Dimensional (3D), computed tomography (CT) scan preoperatively and intraoperatively whereas others used O-arm fluoroscopy and CT scan post-operatively. [19][20][21][22][23][24][25] O-arm and 3D fluoroscopy IGN gave excellent results but they are expensive and may not be affordable for many facilities. 19 There is no article to the best of our knowledge that describes accurate pedicle screw insertion peroperatively in an anatomical deranged spine like lumbar spondylolisthesis using conventional 2D fluoroscopic images by readily available C-arm and without exposing anteriorly displaced posterior elements (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of navigation systems is specifically pronounced in the thoracic spine (95.5% vs. 79.0% acceptable screw placement) and in scoliotic deformities (10). The least benefit might be expected in single level lumbar fusions (6,11). Boon Tow et al demonstrated no improvement in accuracy in single level degenerative listhesis procedures (11).…”
Section: Navigation and Robotics: What's In The Literature?mentioning
confidence: 99%
“…The least benefit might be expected in single level lumbar fusions (6,11). Boon Tow et al demonstrated no improvement in accuracy in single level degenerative listhesis procedures (11).…”
Section: Navigation and Robotics: What's In The Literature?mentioning
confidence: 99%
“…underwent surgical treatment in Japan, USA, and Europe was similar; while that of South Korea, mainland China, and maybe also Taiwan, was younger. The surgery dates in the reports ( Figure 2) [Japan , South Korea (29-38), mainland China (39-41), and Taiwan (42,43), America (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56), Europe (57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)] suggest the patient age differences between South Korea, Japan, USA, and Europe were unlikely caused by the difference of the year of operations.…”
mentioning
confidence: 99%